2023
DOI: 10.1186/s12935-023-03061-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrative evaluation and experimental validation of the immune-modulating potential of dysregulated extracellular matrix genes in high-grade serous ovarian cancer prognosis

Qihui Wu,
Xiaoyun He,
Jiaxin Liu
et al.

Abstract: Background High-grade serous ovarian cancer (HGSOC) is a challenging malignancy characterized by complex interactions between tumor cells and the surrounding microenvironment. Understanding the immune landscape of HGSOC, particularly the role of the extracellular matrix (ECM), is crucial for improving prognosis and guiding therapeutic interventions. Methods and results Using univariate Cox regression analysis, we identified 71 ECM genes associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Recent studies suggest that FAP-targeted therapy can inhibit the proliferation of pancreatic tumor cells [ 24 , 25 ]. In gastric cancer, glioblastoma, and ovarian cancer, overexpression FAP is correlated with poor survival prognosis [ 26 28 ]. This study showed that FAP did not associate with the clinical prognosis of SKCM in TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that FAP-targeted therapy can inhibit the proliferation of pancreatic tumor cells [ 24 , 25 ]. In gastric cancer, glioblastoma, and ovarian cancer, overexpression FAP is correlated with poor survival prognosis [ 26 28 ]. This study showed that FAP did not associate with the clinical prognosis of SKCM in TCGA database.…”
Section: Discussionmentioning
confidence: 99%